A case study: justification of humanitarian intervention / Mohamed Shahrul Fazli Kamarulzaman and Syed Zain Abdul Rahman Alhadad - Kamarulzaman, Mohamed Shahrul Fazli; Abdul Rahman Alhadad, Syed Zain (2007)
The use of force for humanitarian purposes has led to a dilemma to the United Nations and consequently the organization is loosing its significance in settling international disputes. To some, this dilemma poses United Nations as a "harlot" at the disposal of everyone. The doctrine of humanitarian intervention made the United Nations conflicts with its own statutory principles that are Article 2(7) of Charter of United Nations stating on state sovereignty against its preamble of the Charter which deemed human rights (individual sovereignty) as the essential basis of the organization. Kofi Annan, the former Secretary -General of United Nations expresses his concerns; "It has cast in stark relief the dilemma of what has been called humanitarian intervention: on one side, the question of the legitimacy of an action taken by a regional organization without a United Nations mandate; on the other, the universally recognized imperative of effectively halting gross and systematic violations of human rights with grave humanitarian consequences."1 This research concentrates on the justifications of humanitarian intervention by discussing the various definitions to the role of United Nations and other international actors. This research also encompasses several initiatives namely the Just war theory, Blair's Doctrine of International Community and International Commission on Intervention and State Sovereignty report on Responsibility to Protect. On this note Kofi Annan states; "I sought to develop the idea of two notions of sovereignty: one for States, another for individuals. This idea was rooted firmly in the UN Charter, which affirms the sovereignty of States even as it challenges us to save succeeding generations from the scourge of war... How to protect individual lives while maintaining and even strengthening the sovereignty of States has become clearer with the publication of this report. You are taking away the last excuses of the international community for doing nothing when doing something can save lives."2 The motive of this research is to gather and critically discuss issues related to humanitarian intervention. Furthermore, this research aims to shed light on the future of intervention as a right to safeguard human rights and compliment the dilemma by analyzing a workable defined doctrine which fuses both conflicting principles. As forwarded by Kofi Annan; "Just as we have learned that the world cannot stand aside when gross and systematic violations of human rights are taking place, so we have also learned that intervention must be based on legitimate and universal principles if it is to enjoy the sustained support of the world's peoples. This developing international norm in favour of intervention to protect civilians from wholesale slaughter will no doubt continue to pose profound challenges to the international community."3 The significance of this research is to provide a thorough understanding of humanitarian intervention and respond to the unsettled confusions circulating this doctrine. Alas, it is our notion that humanitarian intervention shall be defined and universally accepted as a legal right and not a political tool to interfere in the internal affairs of a sovereign state.